Strategy of Palm-Based Biogas Power Plant Development (Review The Needs and Financing Scheme) - Okta Malinda; Lely Marce Margareta; Ahmad Yani; Natasya Iasa Thintia; Ashari Rajj; Ni Wayan Ernawati; Niara Orcha Thistania; Ali Akbar Putra Alam (Universitas Negeri Semarang, 2023)
The purpose of this study is to provide a strategy for the development of palm based biogas power plant (BPP) seen from the analysis of needs and financing schemes. From the research, it is known the dangers of POME waste to human health and the environment, the benefits of POME as a renewable energy source, the large cost of developing BPP, and the benefits that can be obtained if POME is used as fuel for BPP. In addition, it is also known that there are changes in regulations that reduce the interest of palm oil factory (POF) and investors to develop BPP. From the SWOT analysis conducted, the following strategies are given. The government set a policy that each POF has one BPP or cooperates with other POF to build BPP, reallocated fuel subsidy funds to the development of BPP, and abolished the Minister of Energy and Mineral Resources No. 12/2017 and re-enact the Minister of Energy and Mineral Resources No. 27/2014 in order to increase the interest of POF and investors to build BPP, involve an independent third party as a project supervisor and provide sanctions for project termination if it is identified that the construction qualifications of the materials used are not in accordance with the required standards.